DEVELOPMENT OF WAYS OF MODELLING OF VARIABLES MAGNETIC FIELDS ON THE BASIS OF CONTINUOUS CONDUCTING ENVIRONMENTS - D.J. PARSHIN; M.R. VINOKUROV (Advanced Engineering Research)
In present article the approach to calculation and modelling of the stationary and almost stationary magnetic fields, based on transformation of a vortical magnetic field to a potential field is stated. The fact consisting in representation of a contour is put in a basis of a method, formed thin closed токовой by a string, equivalent concerning a magnetic field outside of his double layer of magnetic charges leaning on this contour.